IPTEKS SISTEM PERSEDIAAN DALAM PENENTUAN HARGA POKOK PENJUALAN BAGI USAHA KECIL MENENGAH DI KECAMATAN MALALAYANG I BARAT KOTA MANADO - Saerang, David Paul Elia; Pontoh, Winston (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2019)
Inventory is a component which reported in financial statement and gives an information about inventory circumstances of a company. Inventory also is a component that absorbs a lot of business capital, so that the security of the inventory must be maintained by a business unit, because the damage / loss of inventory means the lost capital (loss) of the business. The village of Malalayang I in Manado City is one of the regions known as a business-intensive region and also as part of an autonomous region to be specifically observed given that government bureaucracy and public services are considered to have the ability to implement good governance. The implementation of science and technology on inventory management has been carried out and has succeeded in achieving the goal of understanding small entrepreneurs in managing merchandise inventory in the form of applying inventory systems and determining cost of goods sold. Lack of understanding from small entrepreneurs about accounting, especially effective inventory management.